Characterization of polyhydroxyalkanoate production capacity, composition and weight synthesized by Burkholderia cepacia JC-1 from various carbon sources - Chin, Julian Hock-Chye; Samian, Mohd Razip; Normi, Yahaya M. (Elsevier, 2022)
Polyhydroxyalkanoates (PHA) are microbial polymers that have received widespread attention in recent decades as potential alternatives to some petrochemical-based plastics. However, widespread use of PHA is often impeded by its cost of production. Therefore, the search for and systematic investigation of versatile microbial PHA producers capable of using various carbon sources, even in the form of animal fats, for PHA biosynthesis is desirable. This study highlights the PHA production capacity, monomer composition and molecular weight synthesized by Burkholderia cepacia JC-1, a locally isolated strain from soil, from various carbon sources. In the category of simple sugars and plant oils, the use of glucose and palm oil at C:N ratio of 40 resulted in the highest accumulation of 52 wt% and 36 wt% poly(3-hydroxybutyrate) [P(3HB)] homopolymer and dry cell weight of 2.56 g/L and 3.17 g/L, respectively. Interestingly, B. cepacia JC-1 was able to directly utilize animal-derived lipid in the form of crude and extracted chicken fat, resulting in appreciable dry cell weight and PHA contents of up to 3.19 g/L and 47 wt% respectively, surpassing even that of palm oil in the group of triglycerides as substrates. The presence of antibiotics (streptomycin) in cultivation medium did not significantly affect cell growth and polymer production. The supply of sodium pentanoate as a co-substrate resulted in the incorporation of 3-hydroxyvalerate (3HV) monomer at fractions up to 37 mol%. The molecular weight of polymers produced from glucose, palm oil and chicken fat were in the range of 991–2118 kDa, higher than some reported studies involving native strains. The results from this study form an important basis for possible improvements in using B. cepacia JC-1 and crude chicken fats in solid form for PHA production in the future.